2023
DOI: 10.3390/children10030528
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Serum Selenium, Homocysteine, Zinc, and Vitamin D Levels in Febrile Children with and without Febrile Seizures: A Prospective Single-Center Study

Abstract: Objective: Febrile seizure is a complication that makes physicians and families uneasy when detected in children with a high fevers. This study aimed to compare children with febrile seizures and children without seizures in blood selenium, zinc, homocysteine, vitamin D, vitamin B12, and magnesium levels. Materials and Methods: The study group included sixty-one children between the ages of 1–5 who came to the pediatric emergency department with febrile seizure. The control group had 61 children with fever wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…Bhat et al showed that vitamin D deficiency is associated significantly with simple FS, and their recurrence is negatively correlated with low 25OH vitamin D 15 . Çığrı et al proposed that high vitamin D and B12 levels prevent the development of FS in children 3 . Deficiency in vitamin B12 could potentially lower the threshold for seizures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bhat et al showed that vitamin D deficiency is associated significantly with simple FS, and their recurrence is negatively correlated with low 25OH vitamin D 15 . Çığrı et al proposed that high vitamin D and B12 levels prevent the development of FS in children 3 . Deficiency in vitamin B12 could potentially lower the threshold for seizures.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 324 children's medical records were evaluated using a form: age, sex, body mass index (weight/height 2 ), tests [for hemoglobin, RDW, white blood cells, lymphocytes, neutrophils, platelet PLT counts, C-reactive protein (CRP), vitamin B12, D, ferritin, and albumin]. The PNI is calculated as 10 × serum albumin (g/L) +5 × lymphocyte (10 3 cells/μL), and NLR is calculated by dividing the percentage values of neutrophils and lymphocytes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation